Keeping Jerusalem’s Past Alive - Gonen, Rivka (1981)
Jerusalem is not only one of the oldest cities in the world, it is one of the few cities which has been continuously inhabited for more than 40 centuries. From before 1850 B.C., when the first wall surrounded and defended Jerusalem, people have been living there, building homes and markets, temples and palaces, defense […]